2010
DOI: 10.1111/j.1460-9568.2010.07400.x
|View full text |Cite
|
Sign up to set email alerts
|

Morphology, molecular phenotypes and distribution of neurons in developing human corpus callosum

Abstract: The aim of this study was to investigate the morphology, molecular phenotypes, distribution and developmental history of interstitial neurons in the human corpus callosum, here defined as intracallosal neurons. We analysed 26 fetuses, three newborns, five infants and children, and eight adults [age range - 15 weeks postconception (PCW) to 59 years] by means of acetylcholinesterase (AChE) histochemistry and immunohistochemistry for neuron markers (MAP2, NeuN, NPY, calretinin and calbindin). We found a heterogen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
30
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 35 publications
(32 citation statements)
references
References 47 publications
1
30
0
Order By: Relevance
“…This may be related to the dorso-ventrally oriented septa described in the developing human callosum (Jovanov-Miloševic et al, 2010). These have been reported as transient modules; but some indication of what might be comparable septa in the adult macaque can be detected in our PV material (Figure 6).…”
Section: Discussionmentioning
confidence: 76%
See 1 more Smart Citation
“…This may be related to the dorso-ventrally oriented septa described in the developing human callosum (Jovanov-Miloševic et al, 2010). These have been reported as transient modules; but some indication of what might be comparable septa in the adult macaque can be detected in our PV material (Figure 6).…”
Section: Discussionmentioning
confidence: 76%
“…In cats, the number drops from about 570 at birth to 200 in the adult, and the distribution becomes restricted to the rostrum (Riederer et al, 2004). In humans, what were called “intracallosal” neurons are most numerous in the second half of gestation and the early postnatal years, but are found only sporadically in the adult brain (Jovanov-Miloševic et al, 2010). In our adult monkey material, NADPHd+ neurons were sparsely distributed, but readily identified.…”
Section: Discussionmentioning
confidence: 99%
“…More recently, GABAergic (γ-aminobutyric acidergic) neurons and glutamatergic neurons that populate transiently the CSB have also been shown to be involved in guiding callosal axons at the midline [11]. These glial and neuronal guidepost populations are also observed in the human foetal CC [2], [12].…”
Section: Introductionmentioning
confidence: 99%
“…Its absence is associated with an acallosal phenotype, that can be rescued by a 'sling graft,' supporting a major role for this structure in the guidance of callosal axons Katz et al, 1983;Shu and Richards, 2001;Silver and Ogawa, 1983;Silver et al, 1982Silver et al, , 1993. While, the presence of neurons in the corpus callosum was reported in the cat, mouse, and human (Jovanov-Milosevic et al, 2010;Ren et al, 2006;Riederer and Innocenti, 1992;Riederer et al, 2004), recent studies have revealed that the 'glial' sling is largely composed of glutamatergic immature neurons expressing NeuN, b-tubulin, calretinin, Emx1, and NFIA (Niquille et al, 2009;Ren et al, 2006;Shu et al, 2003b). They are generated from E14.5 to P2 and have been proposed to migrate medially from the ventricular zone next to the sling (Figure 25.5; Niquille et al, 2009;Shu et al, 2003b) or from retrobulbar regions (Meyer and Goffinet, 1998;.…”
Section: Tangentially Migrating Neurons In the Development Of The Cormentioning
confidence: 94%